Workplace Barriers to Return-to-Work Processes - Enehaug, Heidi; Spjelkavik, Øystein; Alves, Daniele Evelin; Fure, Silje CR; Howe, Emilie Isager; Andelic, Nada; Løvstad, Marianne (Nordic Journal of Working Life Studies, 2022)
This study identified workplace barriers to return-to-work (RTW) processes through a multiple case study consisting of 38 cases. Sixty-four interviews with employees with mild traumatic brain injury (TBI) and 45 interviews with their managers were conducted in 2017–2020 at T1 (1–3 months after the employees returned to work) and T2 (12–16 months after T1). Workplace barriers were associated with the organizational and psychosocial work environments, TBI knowledge, and char- acteristics of the employee. The role of management was a key aspect across all barriers. Workplace barriers often co-occurred and became increasingly important at T2. At T2, most employees increased their workload, but some still experienced unsupportive management, workplace conflicts, and a low degree of job control. The psychosocial work environment is a main area for workplace barriers. The managers’ knowledge of RTW processes and TBI-related challenges potentially reduce barriers and thereby contribute to balance the needs of the organization and the individual.